Gamma and Beta function extravaganza

Calculus Level 3

0 π 2 csc θ n d θ = α π n 2 β + 1 n Γ ( γ n ) Γ δ ( 1 ϵ n ) \int_{0}^{\frac {\pi}{2}} \sqrt [n] {\csc \theta}\ d\theta = \dfrac {\alpha \pi n \cdot 2^{\beta+\frac 1n}\Gamma\left(\frac \gamma n\right)}{\Gamma^\delta \left(\frac 1{\epsilon n}\right)}

The equation above holds true for integers α \alpha , β \beta , γ \gamma , δ \delta , and ϵ \epsilon , where β > 0 \beta > 0 . Find α β γ δ π + ϵ \alpha \beta \gamma \delta \pi + \epsilon .

10 π + 14 10\pi + 14 4 e 4e 14 π 9 14\pi - 9 11 π + 7 11\pi + 7 7 π e 7\pi e 2 π 2 2\pi - 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Aug 17, 2020

Note: The method used by @N. Aadhaar Murty was correct but computation was incorrect.

I = 0 π 2 csc x n d x = 0 π 2 sin 1 n x cos 0 x d x = 1 2 B ( 1 2 1 2 n , 1 2 ) where B ( ) is the beta function. = Γ ( 1 2 1 2 n ) Γ ( 1 2 ) 2 Γ ( 1 1 2 n ) where Γ ( ) is the gamma function. = π Γ ( 1 2 1 2 n ) 2 ( 1 2 n ) Γ ( 1 2 n ) = π n Γ ( 1 2 n ) Γ ( 1 2 1 2 n ) Γ 2 ( 1 2 n ) By Legendre duplication formula (see note) = π n 2 1 + 1 n π Γ ( 1 n ) Γ 2 ( 1 2 n ) = 2 1 + 1 n π n Γ ( 1 n ) Γ 2 ( 1 2 n ) \begin{aligned} I & = \int_0^\frac \pi 2 \sqrt[n]{\csc x} \ dx \\ & = \int_0^\frac \pi 2 \sin^{-\frac 1n} x \cos^0 x \ dx \\ & = \frac 12 B \left(\frac 12 - \frac 1{2n}, \frac 12 \right) & \small \blue{\text{where }B(\cdot) \text{ is the beta function.}} \\ & = \frac {\Gamma\left(\frac 12 - \frac 1{2n}\right) \Gamma \left(\frac 12 \right)}{2 \Gamma \left(1 - \frac 1{2n}\right)} & \small \blue{\text{where }\Gamma(\cdot) \text{ is the gamma function.}} \\ & = \frac {\sqrt \pi \Gamma\left(\frac 12 - \frac 1{2n}\right)}{2 \left(-\frac 1{2n} \right) \Gamma \left(- \frac 1{2n}\right)} \\ & = - \frac {\sqrt \pi n \blue{\Gamma \left(- \frac 1{2n}\right)\Gamma\left(\frac 12 - \frac 1{2n}\right)}}{\Gamma^2 \left(- \frac 1{2n}\right)} & \small \blue{\text{By Legendre duplication formula (see note)}} \\ & = - \frac {\sqrt \pi n \cdot \blue{2^{1+\frac 1n}\sqrt \pi \Gamma \left(- \frac 1n\right)}}{\Gamma^2 \left(- \frac 1{2n}\right)} \\ & = - \frac {2^{1+\frac 1n} \pi n \Gamma \left(- \frac 1n\right)}{\Gamma^2 \left(- \frac 1{2n}\right)} \end{aligned}

Therefore, α β γ δ π + ϵ = 2 π 2 \alpha \beta \gamma \delta \pi + \epsilon = \boxed{2\pi - 2}


Note: Legendre duplication formula

π Γ ( 2 z ) = 2 2 z 1 Γ ( z ) Γ ( z + 1 2 ) Putting z = 1 2 n π Γ ( 1 n ) = Γ ( 1 2 n ) Γ ( 1 2 1 2 n ) 2 1 + 1 n Γ ( 1 2 n ) Γ ( 1 2 1 2 n ) = π 2 1 + 1 n Γ ( 1 n ) \begin{aligned} \sqrt \pi \Gamma(2z) & = 2^{2z-1}\Gamma(z) \Gamma \left(z + \frac 12\right) & \small \blue{\text{Putting }z = - \frac 1{2n}} \\ \sqrt \pi \Gamma \left(-\frac 1n \right) & = \frac {\Gamma \left(-\frac 1{2n} \right)\Gamma \left(\frac 12 -\frac 1{2n} \right)}{2^{1+\frac 1n}} \\ \implies \Gamma \left(-\frac 1{2n} \right)\Gamma \left(\frac 12 -\frac 1{2n} \right) & = \sqrt \pi \cdot 2^{1+\frac 1n} \Gamma \left(-\frac 1n\right) \end{aligned}

References:

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...